2021
DOI: 10.1039/d1ce00225b
|View full text |Cite
|
Sign up to set email alerts
|

Generality of liquid precursor phases in gas diffusion-based calcium carbonate synthesis

Abstract: The ammonia diffusion method (ADM) is one of the most widely used strategies for the bioinspired synthesis of minerals. Herein, we present investigations of the mineralization mechanism using an advanced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
(55 reference statements)
4
9
0
Order By: Relevance
“…8 gives a schematic overview on the pathways of polymer-controlled calcium carbonate crystallisation observed directly or indirectly in the present work. In many ways, the proposed mechanism of nucleation and subsequent phase transformation is consistent with a series of previous studies on the early stages of CaCO 3 formation: 19–36,40–52,60,61 initially, in the under- and supersaturated one-phase system, calcium and carbonate ions assemble into ion pairs and larger clusters (PNCs) according to the respective equilibrium constants of ion association (Step 1 in Fig. 7).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…8 gives a schematic overview on the pathways of polymer-controlled calcium carbonate crystallisation observed directly or indirectly in the present work. In many ways, the proposed mechanism of nucleation and subsequent phase transformation is consistent with a series of previous studies on the early stages of CaCO 3 formation: 19–36,40–52,60,61 initially, in the under- and supersaturated one-phase system, calcium and carbonate ions assemble into ion pairs and larger clusters (PNCs) according to the respective equilibrium constants of ion association (Step 1 in Fig. 7).…”
Section: Discussionsupporting
confidence: 87%
“…near-neutral) pH. [27][28][29] In the subsequent course of crystallisation, a number of further, more or less transient species have been observed (e.g. amorphous nanoparticles [30][31][32] or metastable crystalline phases [33][34][35] ), and the growth of the final crystals was found to potentially occur via ''non-classical'' mechanisms like particle accretion, 36 oriented attachment, 37 and mesocrystal formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the shape analysis is supported by an inspection of the interfaces at higher magnifications: the droplets present smooth interfaces, whereas the amorphous particles present significant roughness with characteristic size in the nanometer range. However, assigning a liquid state from cryoTEM morphology, although common practice for mineral liquid−liquid phase separation, 18,23,31,40 is indirect and prone to error. Although Liu et al have recently observed identical structures by in situ liquid-cell TEM, they did not conclude on the liquid nature of the high-concentration structures.…”
supporting
confidence: 67%
“…Hopper morphologies are characteristic of diffusion-limited growth, where the vertices of a crystal are exposed to higher concentrations of solutes than the center of the faces, giving rise to faster growth. 27 Consistent with previous work, 32,33 cryogenic transmission electron microscopy (cryo-TEM) revealed that amorphous calcium carbonate (ACC) was the first structure formed in all cases (Figure 1d,e) and that stability of this precursor phase was enhanced for ethanol contents above 50 vol % (Figures S1 and S2). 34,35 Incorporation of Brilliant Blue R Dye within Calcite in Water/Ethanol Mixtures.…”
Section: ■ Resultssupporting
confidence: 88%